Prevalence and predictors of sub-optimal laboratory monitoring of selected higher risk medicines in Irish general practice: a 5-year retrospective cohort study of community-dwelling older adults - Fiona Boland; Emma Wallace; Frank Moriarty; Tom Fahey; Caroline McCarthy; Ann Sinéad Doherty; Mark Feighery (BMJ Open)
Objectives To describe the prevalence of sub-optimal monitoring for selected higher-risk medicines in older community-dwelling adults and to evaluate patient characteristics and outcomes associated with sub-optimal monitoring.Study design Retrospective observational study (2011–2015) using historical general practice-based cohort data and linked dispensing data from a national pharmacy claims database.Setting Irish primary care.Participants 625 community-dwelling adults aged ≥70 years and prescribed at least one higher-risk medicine during the 5-year study period.Primary and secondary outcome measures The primary outcome was the prevalence of sub-optimal laboratory monitoring using a composite measure of published medication monitoring indicators, with a focus on commonly prescribed higher-risk medicines such as diuretics and anticoagulants. Poisson regression was used to assess the patient characteristics associated with sub-optimal monitoring and explanatory variables included the number of medicines, age, sex, deprivation and anxiety/depression symptoms. Logistic regression was used to explore the association between baseline sub-optimal monitoring and the odds of adverse health outcomes (unplanned healthcare utilisation, adverse drug reactions and mortality).Results Of 625 participants, the mean age was 77.7 years, 53% were female, the mean number of drugs was 7.3 (SD 3.3) and 499 (79.8%) had ≥1 unmonitored dispensing over 5 years. The number of drugs, deprivation and anxiety/depression symptoms were significantly associated with sub-optimal monitoring, with the strongest association seen for anxiety/depression symptoms (incidence rate ratio: 1.33, 95% CI 1.05 to 1.68). There was a small but significant association between baseline sub-optimal monitoring and emergency department visits at follow-up, but no evidence of an association with unplanned hospital admissions, mortality or adverse drug reactions.Conclusion The prevalence of sub-optimal medication monitoring was high, and number of drugs, deprivation and anxiety/depression symptoms were significantly associated with sub-optimal monitoring. However, the public health impact of these findings remains uncertain, as there was no clear evidence of an association between sub-optimal monitoring and adverse health outcomes. Further research is needed to evaluate the effect of improved monitoring strategies and the optimal timing for drug monitoring of higher risk medications.